Hacia un liderazgo sostenible, más profundo, más prolongado, más amplio (Towards sustainable, deeper, longer and broader leadership) - Fink, Dean (Revista Eletrônica de Educação, 2019)
The succession of the principals is always a risk for the sustainability of the improvement in the school. Hence the need posed by the author to look for sustainable models of leadership in the educational field that, extrapolating the concept of environmental sustainability, allow preserving learning and keeping moving forward. In this context, he recalls seven basic principles of sustainable leadership: depth, duration, breadth, justice, diversity, inventiveness, and conservation. He emphasizes that sustainable leadership and educational improvement preserve and develop deep learning for everything that spreads and lasts, and they do so not to harm, but to generate benefits for their environment. Resumo A sucessão dos diretores é sempre um risco para a sustentabilidade da qualidade da escola. Por isso a necessidade de o autor buscar modelos sustentáveis de liderança no campo educacional que, extrapolando o conceito de sustentabilidade do ambiente, permite manter o aprendido e seguir avançando. Nesse contexto, ele lembra sete princípios básicos da liderança sustentável: profundidade, duração, abrangência, justiça, diversidade, inventividade e conservação. Enfatiza que liderança sustentável e melhora educacional preservam e desenvolvem o aprendizado profundo para tudo o que se espalha e dura, e fazem isso não para prejudicar, mas gerar benefícios para o seu entorno. Resumen La sucesión de los directivos es siempre un riesgo para la sostenibilidad de la mejora en la escuela. De ahí la necesidad planteada por el autor de buscar modelos sustentables de liderazgo en el ámbito educativo que, extrapolando el concepto de la sustentabilidad medioambiental, permitan preservar y seguir avanzando. En ese contexto, recuerda siete principios básicos del liderazgo sostenible: profundidad, duración, amplitud, justicia, diversidad, inventiva, y conservación. Subraya que el liderazgo y la mejora educacional sostenibles preservan y desarrollan aprendizajes profundos para todo aquello que se propaga y perdura, y lo hacen procurando no dañar, sino generar beneficios para su entorno. Keywords: Succession of principals, Leadership models, Sustainable leadership, Educational improvement. Palavras-chave: Sucessão de diretores, Modelos de liderança, Liderança sustentável, Melhora educacional. Palabras claves: La sucesión de directores, Modelos de liderazgo, Liderazgo sostenible, Mejora educativa. References ADLER P.; KWON, S. Social Capital: Prospects for a new concept, Academy of Management Review, 29 (2), 2002, pp.17-40. APPLE M. Educating the Right Way: Markets, standards, God and inequality. NuevaYork: Routledge, 2006. BALL, S. The Education Debate. Bristol: The Policy Press, 2008. BOURDIEU, P.; WACQUANT, L. An Invitation to Reflexive Sociology. Chicago: University of Chicago Press, 1992. BURCH, P. Hidden Markets: The new education privatization. Nueva York: Routledge, 2009. BUSINE, M.; WATT, B. Succession Management: Trends and current practices, Asia Pacific Journal of Human Resources. 43 (2), 2005, pp.225-237. COLEMAN, J. Social capital and the creation of human capital, American Journal of Sociology, 90 (suplemento), S95-S120, 1988. COLLINS, J.C.; PORRAS, J.I. Built to last: successful habits of visionary companies (3a edición). Londres: Random House Business Books, 2000. DELORS, J.; AL MUFTI, I.; AMAGI, A.; CARNEIRO, R.; CHUNG, F.; GEREMEK, B. et al. Learning: The treasure within - report to UNESCO of the International Commission on Education for the Twenty-first Century. París: UNESCO, 1996. FINK, D. Trust and Verifiy: The real keys to school improvement. Londres: UCL/IOE Press, 2016. FINK, D. The Succession Challenge. Thousand Oaks CA: Cowin, 2010. FINK, D. Leadership for Mortals. Thousand Oaks CA: Cowin, 2005. FUKUYAMA, F. Social capital and the modern capitalist economy: Creating a high trust workplace, Stern Business Magazine, 4(1), 1993, p.17. FULLAN, M. Leadership and Sustainability. System thinkers in action, San Francisco: Jossey-Bass., 2005, ix. GRONN, P. Personal Correspondence, 2009. GRONN, P. Distributed leadership. In: K. Leithwood, P. Hallinger, K. Seashore-Louis, G. Furman-Brown, P. Gronn, W. Mulford W., and K. Riley. (Eds.). Second international handbook of educational leadership and administration. Dordrecht, Países Bajos: Kluwer, 2002. GRONN, P. From transactions to transformations: A new world order in the study of leadership. Educational Management & Administration, 24(1), 1996, pp.7-30. HOPKINS, D.; HIGHHAM, R.; ANTARIDOU, E. School leadership in England Contemporary challenges, innovative responses and future trends. Nottingham: NCSL, 2009. HARGREAVES, A.; FULLAN, M. Professional Capital: Transforming teaching in every school. Nueva York: Teachers College Press, 2012. HARGREAVES, A.; GOODSON, I. Educational change over time? The sustainability and non-sustainability of three decades of secondary school change and continuity, Educational Administration Quarterly. 42 (1), 2006. HARGREAVES, A.; FINK, D. Distributed Leadership: Democracy or Delivery, Journal of Educational Administration, 46 (2), 2008, pp.229-240. HARGREAVES, A.; FINK, D. Sustainable Leadership. San Francisco CA: Jossey Bass, 2006. HARGREAVES, A.; FINK, D. Sustaining leadership. Phi Delta Kappan, 84(9), 2003, pp. 693-700. HARTLEY, D. The emergence of distributed leadership in education; Why Now? British Journal of Educational Studies, 55(2), 2007, p.211. HARRIS, A. Future leadership: Challenges and implications, Invitation Seminar '21st Century Schools' Department for Children, Schools and Families (DCSF) Londres, 27 de marzo, 2009. KNOKE, D. Organizational networks and corporate social capital. In: A. LEENDERS AND S. GABBEY (Eds.) Corporate Social Capital and Liability. Boston: Kluwer, 1999, pp.17-42. KUTSYURUBA, B.; WALKER, K.; NOONAN, B. The ecology of trust in the principalship, Journal of Educational Administration and Foundations, 21(1), 2010, pp.23-47. LEANA, E. The missing link in school reform, Stanford Social Innovation Review, 2011. En línea, http://www.ssireview.org/articles/entry/the_missing_link_in_school_reform, (consultado el 28 de agosto de 2014). LEITHWOOD, K.; JANTZI, D.; MASCALL, B. Large-scale reform: What works? Toronto: University of Toronto Press, 1999. LEVIN, B. Governments and education reform: Some lessons from the last 50 years, Journal Education Policy, (25), 2010, pp.739-747. LEWICKI R.; MCALLISTER, D.; BIES R. Trust and Distrust: New relations ships and realities, Academy of Management Review, (23), 3, 1998, pp.438-458. LIN, N. Social networks and status attainment, Annual Review of Sociology, 25, 1999, pp. 467-487. MACMILLAN, R. Leadership succession, culture of teaching, and educational change. In: N. BASCIA, & A. HARGREAVES (Eds.), The Sharp Edge of Educational Change. Londres: Falmer Press, 2000. MCCALL, M. Developing executive through work experience, Human Resources Planning. 11 (1), 1988, pp.1-11. MINTZBERG, H Managers not MBAs: A hard look at the soft practice of managing and management development. San Francisco CA: Berrett-Koehler Publishers, 2004. POSTMAN, N. The Disappearance of Childhood. Nueva York: Vintage Books, 1984. PUTNAM, R. Bowling alone: America’s declining social capital, Journal of Democracy. 6 (1), 1995, pp.65-78. ROSENBERG, T. Join the Club: How peer pressure can change the world. Nueva York: W. W. Norton, 2011. SUZUKI.D. The David Suzuki Reader; A lifetime of ideas from a leading activist and thinker. Vancouver: Greystone Press, 2003. TSCHANNEN-MORAN, M. Trust Matters: Leadership for successful schools. San Francisco, CA: Jossey–Bass, 2004. UNITED NATIONS United Nations Decade of Education for Sustainable Development, 2005-2014: borrador de esquema de implementación; París, UNESCO, 2004. WORLD COMMISSION ON ENVIRONMENT AND DEVELOPMENT. Our Common Future. Nueva York: Asamblea General de las Naciones Unidas, 1987.